PENINGKATAN PENGETAHUAN HUKUM BISNIS TERHADAP MARKET PLACE - Irene Svinarky; Saut Pintubipar Saragih; Mesri Silalahi (ASOSIASI IDEBAHASA KEPRI, 2023)
The activity of Tridharma in Bengkong has been conducted by the team of lecturer and involved women participants (housewives). The job of these women are varied from housewives, traders and working as labour or staff in a company. The target of this activity is to provide knowledge to the participants especially housewives who know more about the Marketplace in the online media, because many of them working as trader and also working in companies. The use of media via mobile phone can be used in business transactions, by marketing through shoope, tiktok and several other media. The purpose of this activity is in the form of: a method of online transaction through a clear and more secure registered Marketplace so that consumers are not harmed and increase income for sellers who sell goods at the Marketplace. This method of implementing activity is carried out by practicing directly to the participants how to use their social media to earn money. Furthermore, at the second meeting, counseling of buying and selling practices will be held online through the media tiktok. The Marketplace that the team intended is not only in the form of sales on social media, but we can use social media accounts as a place to find additional income. The participants are trained to communicate better in front of the public by broadcasting live on the Marketplace.